Upper extremity motor quality evaluation in children with Cerebral Palsy - Haryelle Náryma Confessor Ferreira; Gabriele Natane de Medeiros Cirne; Silvana Alves Pereira; Núbia Maria Freire Vieira Lima; Roberta de Oliveira Cacho; Enio Walker Azevedo Cacho
Abstract Introduction: Cerebral Palsy (CP) is a non-progressive disorder that may compromise functional abilities of the upper limbs due to motor and sensitive loss, that are still poorly evaluated and described by reliable tools. Objective: This study aimed to evaluate motor quality and skills of the upper extremity in children with CP in regions of Trairi and Seridó from Rio Grande do Norte state (Brazil). Methods: It is a cross-sectional exploratory study, with a qualitative approach, with 17 children with CP, aged between four and eight years. The following instruments were used for upper extremity evaluation: Manual Ability Classification System (MACS), Quality of Upper Extremity Skills Test (QUEST) and Gross Motor Function Classification System (GMFCS). Results: Mean and standard deviation (sd) of QUEST total score and the domains dissociated movement, grasp, weight bearing and extensive protection were, respectively, 41.06/37.08; 53.12/34.50; 15.51/62.98; 37.76/37.52; 42.48/47.26. MACS and GMFCS median scores were, respectively, 3 (three) and 5 (five); high positive correlation was observed between MACS and GMFCS (rs=0.83) and high negative correlation between GMFCS and total QUEST (rs=-0.83), as well as between MACS and QUEST (rs=-0.84); and MACS and all QUEST domains (rs=-0.73; rs=-0.82; rs=-0.76; rs=-0.79), p<0.001. Conclusion: Children with CP showed deficit in motor quality and skills of the upper limb, allowing to infer functional limitations regarding manipulation of objects and consequent dependence during life activities.